Elderly Class (Yoga, Acupressure, and Progressive Muscle Reflexology) to Improve the Health of the Elderly in Tambakmulyo Village, Puring, Kebumen - Kusumastuti, Kusumastuti; Muthoharoh, Siti; Rahmadhani, Wulan (Journal of Community Services and Engagement: Voice of Community (VOC), 2024)
An elderly person is someone who has reached the age of 60 years and over. The elderly are an age group of humans who have entered the final stages of their life. The increase in the number of elderly people has impacts, including the emergence of degenerative disease problems that often accompany the elderly, which are chronic and multipathological, such as hypertension, heart defects, diabetes mellitus, uterine/prostate cancer, osteoporosis and others, the treatment of which takes quite a long time. and huge costs. It is hoped that the elderly class for elderly health will grow the elderly's own ability to overcome health problems with the support and guidance of professional staff, towards realizing a healthy elderly life. The design of activities to achieve goals is planning, action, evaluation and follow-up. In detail the methods and mechanisms. The results of the activity refer to previously determined output targets, namely that seniors can take part in senior classes and can increase seniors' knowledge regarding Yoga, Accrupressure and Progressive Muscle Reflexology. Yoga, acupressure and ROP training will increase the elderly's knowledge, which will also influence the accuracy of yoga, acupressure and ROP training. By receiving training, it is hoped that seniors will understand and be skilled in applying yoga, acupressure and ROP.